Novel Ethyl 1,5-Disubstituted-1H-Pyrazole-3-Carboxylates as a New Class of Antimicrobial Agents - Radwan Awwad A.; Ghorab Mostafa M.; Alsaid Mansour S.; Alanazi Fares K. (Acta Pharmaceutica, 2014)
A series of pyrazole derivatives 9-22 were designed and synthesized. All the newly synthesized compounds were assayed for their antimicrobial activity against the Grampositive bacteria Staphyllococcus aureus and Bacillius subtilis and the Gram-negative bacteria Escherichia coli, Pseudomonas aeruginosa, in addition to the fungi organisms, Candida albicans, C. parapsilosis and C. tropicalis. Ethyl 5-(2,5-dimethylthiophen- 3-yl)-1-phenyl-1H-pyrazole-3-carboxylate (21) (MICE.coli = 0.038 μmol mL-1, MICP. aerug. = 0.067 μmol mL-1) is nearly as active as ampicillin (MIC = 0.033 and 0.067 μmol mL-1), respectively. Ethyl 5-(4-bromo-2-chlorophenyl)- 1-phenyl-1H-pyrazole-3-carboxylate (16) (MIC = 0.015 μmol mL-1) is more active than fluconazole (0.020 μmol mL-1) as a reference drug against C. parapsilosis.